THE IMPORTANCE OF TECHNOLOGY IN EDUCATION DURING THE COVID-19 PANDEMIC PERIOD - Sadala, Daniel; Gibertoni, Daniela (Revista Interface Tecnológica, 2021)
In December 2019, China notified the World Health Organization (WHO) about the epidemic of a virus similar to viral pneumonia in Wuhan province. In March 2020, a pandemic state was declared in all corners of the world due to the high infectivity of the new coronavirus, in order to mitigate its great contamination, authorities from all over the world, including in Brazil, chose to adopt maneuvers aimed at minimizing contagion, one of these maneuvers was social isolation, making traditional routines a little more flexible, as in the case of distance learning. Through a bibliographic survey, we sought to ascertain the main impacts of technology on education in the pandemic period of COVID-19.
Keywords: Technology; Importance; COVID; Education